Correction: Escape of anions from geminate recombination in THF due to charge delocalization. Issue 5 (23rd January 2018) - Chen, Hung-Cheng; Cook, Andrew R.; Asaoka, Sadayuki; Boschen, Jeffery S.; Windus, Theresa L.; Miller, John R.
Abstract : Correction for 'Escape of anions from geminate recombination in THF due to charge delocalization' by Hung-Cheng Chen et al., Phys. Chem. Chem. Phys., 2017, 19, 32272–32285.